PENGARUH APLIKASI BAHAN PEMBENAH TANAH ALAMI TERHADAP PH TANAH DAN KETERSEDIAAN N, P, K PADA TANAH SAWAH - Etik Puji Handayani (STIPER Dharma Wacana Metro, 2014)
Soil amelioran contribute to improving paddy soil nutrient availability. It is important to achieve food self-sufficiency in Indonesia. The objectives of this study was to evaluate the effect of the application of soil amelioran on soil pH and nutrient status of , P, and K in paddy soil. The research was conducted in the laboratory STIPER Dharma Wacana Metro from March to June 2012. The experiment was arranged in a completely randomized design with three replication . there are 48 experimental units that a combination treatment of rice straw (0,5, 10, 15 ton/ha), straw ash (equivalent to burning 0,5,10,15 ton/ha of rice straw, and source of Ca (without Ca, CaCO3, and steel slag). The result showed that (1) there was a tendency in the soil pH to be higher with increasing dose amelioran and (2) there was indicate for increasing the availability of N, but not for the availability of P, and K.Keywords; Amelioran Rice Straw, Source Ca, Availability of Nutrient, Paddy Soil